Analysis of Factors Related to The Documentation of Nursing Care - Mayenti, Fitra; Arif, Yulastri; Priscilla, Vetty (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Nursing documentation is written evidence of the implementation of nursing care, but in some hospitals documenting nursing care is still problem and far from the Indonesian Ministry of Health, Which is 80%. This study aimed to determine the factors associated with Nursing documentation of inpatient care at the Ibnu Sina Islamic Hospital Pekanbaru. The design of this study was observational cross sectional. A sample of 82 nurses used a proportional random sampling technique.The results showed that there individual factors 72 % were early adult nurses, 51,2 % were old nurse with long time, 95,1% were high educational level. Organization factors showed that there 70,7 % were head nurse good category, 75,5% were employee available category, 52, 4% were nursing care good category.There were significant differences of length of work and level of education with documentation of nursing care.